Transcriptome Profiling of Human Follicle Dermal Papilla Cells in response to Porphyra-334 Treatment by RNA-Seq. (13th January 2021) - Kim, Su Yeon; Cho, Won Kyong; Kim, Hye-In; Paek, Seung Hye; Jang, Sung Joo; Jo, Yeonhwa; Choi, Hoseong; Lee, Jeong Hun; Moh, Sang Hyun
Abstract : Porphyra-334 is a kind of mycosporine-like amino acid absorbing ultraviolet-A. Here, we characterized porphyra-334 as a potential antiaging agent. An in vitro assay revealed that porphyra-334 dramatically promoted collagen synthesis in fibroblast cells. The effect of porphyra-334 on cell proliferation was dependent on the cell type, and the increase of cell viability by porphyra-334 was the highest in keratinocyte cells among the three tested cell types. An in vivo clinical test with 22 participants demonstrated the possible role of porphyra-334 in the improvement of periorbital wrinkles. RNA-sequencing using human follicle dermal papilla (HFDP) cells upon porphyra-334 treatment identified the upregulation of metallothionein- (MT-) associated genes, confirming the antioxidant role of porphyra-334 with MT. Moreover, the expression of genes involved in nuclear chromosome segregation and the encoding of components of kinetochores was upregulated by porphyra-334 treatment. Furthermore, we found that several genes associated with the hair follicle cycle, the hair follicle structure, the epidermal structure, and stem cells were upregulated by porphyra-334 treatment, suggesting the potential role of porphyra-334 in hair follicle growth and maintenance. In summary, we provided several new pieces of evidence of porphyra-334 as a potential antiaging cosmetic agent and elucidated the expression network in HFDP cells upon porphyra-334.